Common-law principles in consent for patients in oral and maxillofacial surgery who lack mental capacity: do we know them all?. Issue 9 (November 2015) - Shekar, V.; Jabbar, J.; Mitchell, D.A.; Brennan, P.A.
Abstract: Over the last 5 years, the medical profession has relied on the Bolam test for their defence in cases of clinical negligence. While still a matter of controversy between health professionals and legal experts, the Bolam test has been tried and criticised not only by the English courts but also in the United States, Canada, and Australia. In the medical profession the concept of the law of consent has moved away from a doctrine of professional paternalism towards patient-focused paternalism, and has increased the emphasis on human rights and the autonomy and choice of the patient. These changes present a challenge to health professionals, and a lack of effective recognition and interpretation can result in non-compliance. We review the developments in the law of consent since Bolam and discuss how they affect patients with incapacity, and highlight the importance of being familiar with them.